Adaptive finite element simulation of currents at microelectrodes to a guaranteed accuracy. ECE and EC2E mechanisms at channel microband electrodes - Harriman, K; Gavaghan, D; Houston, P; Kay, D; Suli, E (2000)
We extend the work in the accompanying paper (K. Harriman et al., Electrochem. Commun. 2 (2000) 567) on the use of adaptive finite element methods to simulate the current for a steady state E reaction mechanism at a channel microband electrode to the more complex ECE mechanism, and the non-linear EC2E mechanism. We again use the standard Galerkin approach for the diffusion dominated (low-flow) case, and the streamline diffusion finite element method (SDFEM) for convection-dominated (high-flow) case, and compare our results with previous numerical and analytical approximations. We give a general discussion on the implications o